2007
DOI: 10.1093/ndt/gfl848
|View full text |Cite
|
Sign up to set email alerts
|

Use of pure bicarbonate-buffered peritoneal dialysis fluid reduces the incidence of CAPD peritonitis

Abstract: Our results suggest that the pure bicarbonate-buffered peritoneal dialysis fluid appears to reduce the frequency of peritonitis in CAPD patients possibly in relation to greater biocompatibility and maintenance of peritoneal membrane structural integrity. Similar results can probably relate to all low-GDP solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 21 publications
4
38
1
2
Order By: Relevance
“…24,29,30 In this investigation, biocompatible (Balance) solution was associated with an important reduction in peritonitis risk. Similar findings have been reported in 3-year 31 and 5-year 32 nonrandomized studies of biocompatible fluid. In contrast, previous small, single-center randomized controlled trials 8,[12][13][14][15][16][17][18][19] have not shown significant differences in peritonitis rates, possibly due to insufficient statistical power, short follow-up durations, low peritonitis rates, Neyman bias, and drop-outs due to anuria.…”
Section: Discussionsupporting
confidence: 88%
“…24,29,30 In this investigation, biocompatible (Balance) solution was associated with an important reduction in peritonitis risk. Similar findings have been reported in 3-year 31 and 5-year 32 nonrandomized studies of biocompatible fluid. In contrast, previous small, single-center randomized controlled trials 8,[12][13][14][15][16][17][18][19] have not shown significant differences in peritonitis rates, possibly due to insufficient statistical power, short follow-up durations, low peritonitis rates, Neyman bias, and drop-outs due to anuria.…”
Section: Discussionsupporting
confidence: 88%
“…Using negative binomial regression to adjust for age, sex, nasal staphylococcal carriage, cause of end-stage renal failure, weekly Kt/V, and a 3-point subjective nursing assessment of the patients' PD skills and ability, biocompatible fluid use was associated with a significant reduction in the risk of peritonitis (adjusted odds ratio: 0.64; 95% CI: 0.43 to 0.98) (33). Similar findings were observed when the results were expressed as patient-exchanges (0.30 vs 0.50 peritonitis episodes per 1000 patient-exchanges; adjusted odds ratio: 0.65; 95% CI: 0.43 to 0.98).…”
Section: Discussionmentioning
confidence: 99%
“…Duranay et al compared peritonitis rates for 147 patients treated with glucose, icodextrin, and amino-acid-based solutions and concluded that the type of PD solution does not appear to be a risk factor for development of peritonitis (136). Montenegro et al studied 100 incident PD patients treated with either lactate-or pure bicarbonatebuffered solutions (137) and found peritonitis rates 624 PIRAINO et al NovEMBER 2011 -voL. 31, No.…”
Section: Pd Solutionmentioning
confidence: 99%